Coupling of replication type histone mRNA levels to DNA synthesis requires the stem-loop sequence at the 3' end of the mRNA. - Levine, B J (1987)
The role of the 3' end of mRNA in coupling between the level of histone mRNAs and DNA synthesis was examined. We introduced modified mouse histone H3 genes into mouse fibroblasts and studied the regulation of several different H3 mRNAs that are not terminated with a normal histone 3' end. In two cases, the stem-loop sequences were deleted from the mRNAs and replaced either by 3' sequences flanking the H3 gene or by globin 3' untranslated region sequences including the polyadenylylation signal. In the former case, approximately equal to 50% of the modified mRNA was polyadenylylated, whereas in the latter case all of the mRNA had a polyadenylylated terminus. In contrast to the normal histone mRNAs, these mRNAs, including the nonadenylylated form, were stable when DNA synthesis was inhibited with several drugs. The levels of two other histone mRNAs, each containing the stem-loop sequences as an internal part of the mRNA, also were stable when DNA synthesis was inhibited. These results indicate that the posttranscriptional coupling of histone mRNA levels to DNA synthesis requires the presence of the stem-loop sequences at the 3' end of the mRNA.